Perancangan dan Implementasi Sistem Aplikasi Penjualan Sparepart Bus dan Truk Berbasis Web Menggunakan Framework Laravel - Hertanto Mulianto; Eko Sediyono (Lembaga Penelitian dan Pengabdian pada Masyarakat (LPPM) STMIK Global Informatika MDP, 2023)
Toko Kartika Motor Tegal is a shop that offers various kinds of spare parts for buses and trucks. We provide all kinds of spare parts for buses and trucks for purchase by the general public, especially residents of Tegal city. However, there is still no online transaction application for sales and purchases. The purpose of this study is to develop and implement a web-based spare parts sales system application for Toko Kartika Motor Tegal using the Laravel framework. Therefore, Toko Kartika Motor Tegal developed a web-based prototype application to sell spare parts for buses and trucks. The application can enable customers to easily purchase and search for spare parts without going to the store in person. This is the result of design considerations for this application.